Animals on film : possibilities for Malaysian cinema - Teo, Peuh Ing (Universiti Malaysia Sarawak (UNIMAS), 2013)
This research explores the possibilities of using animals as main characters of subject matter in Malaysian cinema. Animal films often involve a sentimental story revolving around a famliy melodrama. The research objectives include the analysis of successful examples of international animal films and the potential to bring such successful techniques to the Malaysian film industry, with the hope of promoting animal films as a viable genre in Malaysia. The research has been applied to a locally-produced short animal p\film, starring a horse, entitled "Budak Kampung"